Agent-based computational demography and microsimulation using JAS-mine - Richiardi, M; Richardson, R (Springer International Publishing, 2017)
In this chapter we provide a hands-on guide on how to build a microsimulation using JAS-mine, a Java-based platform that provides unique simulation tools for discrete-event simulations, including both agent-based and microsimulation models. After presenting the rationale for the recent developments of the JAS-mine project and the main architectural choices made, we illustrate a step-by-step implementation of a rich dynamic microsimulation, which includes demographic processes (birth, death, household formation and dissolution) and other life course events (educational choices, labour market participation and employment outcomes).